Pupil Dilation Dynamics in Serious Game Emotional Activation - Cala, Federico; Gursesli, Mustafa Can; Tarchi, Pietro; Frassineti, Lorenzo; Guazzini, Andrea; Lanata, Antonio (IEEE Games, Entertainment, Media Conference, 2024)
Gaming is becoming a beneficial context in educational and therapeutic applications. Serious game development aims to propose innovative, dynamic biofeedback-engaging games that integrate cognitive information. In this context, pupillometry represents a non-invasive, cost-effective methodology to analyse the activity of the autonomic nervous system and indirectly measure arousal and cognitive load. This study proposes the investigation of pupillometry signal dynamics acquired from a group of healthy subjects during a matching pairs card game session. Lyapunov's theory has been applied to evaluate the nonlinear content of pupillometry dynamic. The emotional states of involved subjects have been assessed through the PANAS scale. Statistical analysis showed that game playing significantly increased positive emotions and, concurrently, decreased negative ones. Spearman correlation analyses showed a significant relationship between arousal and Large Lyapunov Exponent, negative emotions and standard deviation of pupil diameter. Moreover, the latency of the maximum pupil dilation significantly differed in players with high-performance scores compared to low-performance subjects. This outcome seems to validate the use of serious games for future investigation of memory skills and deficits and emotion regulation strategies in both clinical and consumer applications.